A Study of the challenges faces in the implementation of ISO 9001:2008 standards : a case of the Teachers Service Commission of Kenya - Kuria, Kennedy Kariuki (Strathmore University, 2012)
Quality service is one of the aspirations that has become of the corporate scene today and most organisation/-are directing their resources and efforts towards achieving customers' satisfaction. This has seen even the public institutions implementing programmes focused on the quality service as opposed to just providing public service. The purpose of this study was to establish the challenges facing the Teachers' Service Commission of Kenya in the implementation of the ISO 9001 :2008 Standard. This is a standard which gives guidelines on the processes which, if adopted will help an organisation improve the quality of services it commission for less than six years now. The approach that was used to carry out this research was through the use o(priniary dataarid where questionnaires were administered to the '-.,-__ ,0/"/" Teachers Service Commission staff members involved with the ISO 9001:2008 Standard implementations (ISO Team). The findings were later analysed using Statistical Package for Social Sciences and the Microsoft Office Excel. According to the study, the attitude of human resource has emerged as one of the most challenging issues in the implementation of ISO Standards in the Teachers Service Commission. One of the imminent issues that were observed included the role of the top management commitment in the organisations towards the achievement of the set policies and procedures and ensuring that the other staff have the adequate information on the processes. The ISO process is an important milestone and if observed well can help an organisation to greater heights of quality management for quality
Undergraduate project